PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Indomaret di Kabupaten Pati) - Mochamad Zit Choirony, 13.05.51.0078; Suko Priyono, Bambang (Students' Journal of Economic and Management, 2018)
The purpose of this research is to know the influence of leadership, motivation and komepnsasi on employee performance at Indomaret in Regency Pati Population in this research is 239 employees Indomaret Pati Regency. While the sample in this study as many as 110 employees. Sampling in this research is purposive sampling that is sampling technique based on criteria. Technique of data test used is test of validity, reliability test, multiple linear regression test, hypothesis test and coefficient of determination. The results showed the number of coefficient of determination doubled (Adjusted R2) of 0,581. This means that 58.1% can be explained by leadership, motivation, and compensation can affect employee performance (Y). While the rest of 41.9% is explained by other variables outside this research variable. The variables of leadership style, motivation, and compensation partially have a positive effect on employee performance means the better the leadership style, the stronger the motivation and the higher the compensation, then the performance of Indomaret employees in Pati Regency will increase. Keywords: Leadership, Motivation, Compensation, Employee Performance